2016
DOI: 10.1097/aln.0000000000000985
|View full text |Cite
|
Sign up to set email alerts
|

Providing Anesthesia Care in Resource-limited Settings

Abstract: Background Anesthesia is integral to improving surgical care in low-resource settings. Anesthesia providers who work in these areas should be familiar with the particularities associated with providing care in these settings, including the types and outcomes of commonly performed anesthetic procedures. Methods The authors conducted a retrospective analysis of anesthetic procedures performed at Médecins Sans Frontières facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…As an example of this type of information, a retrospective MSF study in resource-limited settings demonstrated that general anaesthesia with intubation carries mortality risk as compared with other anaesthetic techniques. 46 …”
Section: Discussionmentioning
confidence: 99%
“…As an example of this type of information, a retrospective MSF study in resource-limited settings demonstrated that general anaesthesia with intubation carries mortality risk as compared with other anaesthetic techniques. 46 …”
Section: Discussionmentioning
confidence: 99%
“… 7 , 12 , 32 , 33 An increase in anesthetic mortality in LMICs is not surprising considering the deficiencies of anesthetic equipment, drugs, basic monitors, safety protocols, and well-trained anesthesiologists and anesthetists. 4 , 34 Although resources are slowly improving, it seems reasonable that every effort should be made in these countries to use the anesthetic techniques that are safest under the present conditions. The few studies from developing countries that exist show a lower risk of death in patients receiving regional instead of general anesthesia.…”
Section: Can Regional Anesthesia Improve Perioperative Safety and Accmentioning
confidence: 99%
“…MSF actions are guided by medical ethics and the principles of independence, neutrality and impartiality. MSF has an important experience in the provision of surgical care, including safe anesthesia, in highly challenging settings – this experience principally relies on a wide flexibility, and delivery of relatively standardized care, which is only minimally tailored to a given setting; and also, for which standard operative procedures have been developed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%